Land and the housing affordability crisis: landowner and developer strategies in Luxembourg's facilitative planning context. Issue 10 (13th October 2022) - Paccoud, Antoine; Hesse, Markus; Becker, Tom; Górczyńska, Magdalena
Abstract: The issue of land and its ownership remains under-explored in relation to the housing affordability crisis. We argue that the concentrated ownership of residential land affects housing production in Luxembourg through the interplay of landowner and developer wealth accumulation strategies. Drawing on expert interviews, we first show that the country's growth-centred ecology has produced a negotiated planning regime that does little to manage the pace of residential development. Through an investigation of the development of 71 large-scale residential projects since 2007, we then identify the private land-based wealth accumulation strategies this facilitative planning regime enables. This analysis of land registry data identifies land hoarding, land banking and the strategic use of the planning system. The Luxembourg case – with its extremes of land concentration, low taxes and public disengagement from land – provides a glimpse at the influence of landowner and property developer strategies on housing affordability free of the usual mediating impact of the planning system.